Faktor – Faktor Yang Mempengaruhi Initial Public Offering Underpricing (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research was conducted to analyze the influence of the Auditor's Reputation, Intellectual Capital Disclosure, Profitability and Leverage on IPO Underpricing. The data used in this study were taken from the company's prospectus at the time of the initial public offering which was available on the Indonesia Stock Exchange website. There are 70 samples tested, consisting of companies that made initial public offerings in the 2017-2019 period. The sample data collection technique used purposive sampling. The data were processed using statistical analysis tools, Statistical Package for the Social Sciences (SPSS) ver 25.0. Multiple linear analysis is used to test the hypothesis. The results of this study found that only Auditor's Reputation and Profitability had a significant negative effect on IPO Underpricing, while Intellectual Capital Disclosure and Leverage had a positive and insignificant effect on IPO Underpricing.